2005
DOI: 10.1074/jbc.m410026200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cystic Fibrosis Transmembrane Regulator Trafficking and Protein Expression by a Rho Family Small GTPase TC10

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR)-interacting protein, CFTR-associated ligand (CAL) down-regulates total and cell surface CFTR by targeting CFTR for degradation in the lysosome. Here, we report that a Rho family small GTPase TC10 interacts with CAL. This interaction specifically up-regulates CFTR protein expression. Co-expression of the constitutively active form, TC10Q75L, increases total and cell surface CFTR in a dose-dependent fashion. Moreover, co-expression of the dominant-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 37 publications
(54 reference statements)
4
86
0
Order By: Relevance
“…This same region of PIST has been reported to mediate interactions with TC10, a Rho GTPase, (20) and syntaxin-6, a Q-SNARE (23). Recently, exogenous expression of TC10 has been proposed to regulate cystic fibrosis transmembrane conductance receptor trafficking and expression through its interaction with PIST (34). Therefore, binding of golgin-160, TC10, and syntaxin-6 to PIST may coordinate membrane trafficking of some plasma membrane proteins in cell types where these proteins are expressed.…”
Section: Discussionmentioning
confidence: 99%
“…This same region of PIST has been reported to mediate interactions with TC10, a Rho GTPase, (20) and syntaxin-6, a Q-SNARE (23). Recently, exogenous expression of TC10 has been proposed to regulate cystic fibrosis transmembrane conductance receptor trafficking and expression through its interaction with PIST (34). Therefore, binding of golgin-160, TC10, and syntaxin-6 to PIST may coordinate membrane trafficking of some plasma membrane proteins in cell types where these proteins are expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CFTR, the effect is mediated by reductions in the rate of membrane insertion and in the half-life of the channels at the cell surface (21), and can be prevented by blocking endocytosis or lysosomal degradation (25). The negative effect of CAL overexpression on CFTR expression levels can also be reversed by the simultaneous overexpression of NHERF1, which competes for the C-terminal TRL binding motif (21), or by overexpression of TC10, a Rho GTPase whose constitutively active form redistributes CAL intracellularly toward the plasma membrane (26).…”
mentioning
confidence: 98%
“…Later studies showed that TC10 activity is coupled to vesicle fusion at the plasma membrane (Cheng et al 2005;Kawase et al 2006). Together, a conserved function of Cdc42/TC10 family proteins in exocytosis seems to be emerging.…”
Section: The Rho Family Of Small Gtp-binding Proteinsmentioning
confidence: 99%